Me4DCAP V0.1: A method for the development of Dublin Core Application Profiles - Malta, Mariana Curado (2013)
Recent studies show that there is no method to develop a Dublin Core Application Profile (DCAP). A DCAP is a very important construct to implement interoperability, therefore it is essential to have a method to be able to develop such a construct, in order to give DCAP developers a common ground of work. This paper presents the first version of a method to develop Dublin Core Application Profiles (Me4DACP V0.1) that has been developed in a PhD project with a Design Science Research (DSR) approach. Me4DCAP was built having as starting point the Singapore Framework for DCAP and shows the way through the DCAP development. It encompasses a group of pre-defined interconnected activities, explicitly states when they should take place, what techniques could be used to execute them and what artifacts should result from their execution.